SUPPORT SYSTEM SELEKSI ANGGOTA KOPERASI MERAH PUTIH DESA BANDAR RAHMAT MENGGUNAKAN METHOD EDAS - Andre Irfan Ramadhan Safaruddin; Dewi Maharani, M.Kom; Santoso, M.M (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The member selection process at Koperasi Merah Putih Desa Bandar Rahmat is still carried out manually, making it time-consuming and prone to subjective decision-making. This study aims to design and develop a web-based Decision Support System (DSS) to assist cooperative administrators in determining the eligibility of prospective members more objectively and efficiently. The method applied is Evaluation Based on Distance from Average Solution (EDAS), a multi-criteria decision-making method that evaluates alternatives based on their distance from the average value of each criterion. Research data were collected through observation, interviews, and documentation. The system was developed using PHP and MySQL and designed with the Unified Modeling Language (UML) approach. The EDAS calculation process includes decision matrix formation, average value calculation, Positive Distance from Average (PDA), Negative Distance from Average (NDA), normalization, and Appraisal Score computation to produce candidate rankings. The results indicate that the developed system is capable of managing candidate data and conducting the selection process in a structured manner. The implementation of the EDAS method generates objective eligibility rankings based on predetermined criteria. Furthermore, system testing demonstrated that all system functions operated properly. The proposed system can support cooperative administrators in accelerating the selection process, improving transparency, and reducing subjectivity in decision-making.